Let u=inside of square root, so let u=(x-2) and then du=dx and 2x-3= 2(u+2)-3 = 2u+1 so then the integrand becomes
(2x-3)*sqrt(x-2)= (2u+1)*sqrt(u) = (2u+1)*u^1/2 then distribute to get 2u^(3/2)+1u^(1/2) then use the power rule and finally end up with 4/5*u^(5/2)+2/3*u^(3/2)+C and finally plug back in u=x-2
2006-12-20 12:21:33
·
answer #1
·
answered by a_math_guy 5
·
0⤊
0⤋
So you want to solve
Integral [(2x - 3) (x - 2)^(1/2)]dx
There are many methods of doing this, but one thing you can use is u substitution in a slightly different manner than usual.
Let u = x - 2.
What we want to do is manipulate this expression into what it is being multiplied to. We want to try and get 2x - 3 from that, and we can.
u + 2 = x
2(u + 2) = 2x
2u + 4 = 2x
2u + 1 = 2x - 3
Therefore
2du = 2dx, and
du = dx
Integral [(2x - 3) (x - 2)^(1/2)]dx, after u substitution, becomes
Integral [(2u + 1)u^(1/2)] du
Note that at this point, we can actually multiply the monomial u^(1/2) with the binomial. Remember that 2u times u^(1/2) means we can add the exponents, to get 2u^(3/2).
Integral [2u^(3/2) + u^(1/2)]du
Now, we can split this integral of a sum to the sum of two integrals.
Integral (2u^(3/2))du + Integral (u^(1/2))du
And we can pull out all constants; in this case there's just the 2.
2 * Integral (u^(3/2))du + Integral (u^(1/2))du
And now we easily integrate this using the reverse power rule.
2 * (2/5)(u^(5/2)) + (2/3)u^(3/2) + C
Combining the constants,
(4/5)(u^(5/2)) + (2/3)u^(3/2) + C
And now, since we let u = x - 2, our final answer is
(4/5)( [x - 2]^(5/2) ) + (2/3) ( [x - 2]^(3/2) ) + C
We can simplify this even more by factoring, but this should be a good enough answer when it's time for the final exam.
2006-12-20 20:39:29
·
answer #2
·
answered by Puggy 7
·
0⤊
0⤋
Let
u = x - 2
x = u + 2
du = dx
â«(2x-3)sqrt(x-2)dx = â«(2u+4-3)sqrt(u)du = â«(2u+1)sqrt(u)du
= â«[(2u^(3/2) + u^(1/2)]du = (4/5)u^(5/2) + (2/3)u^(3/2) + C
= (4/5)(x - 2)^(5/2) + (2/3)(x - 2)^(3/2) + C
2006-12-20 20:33:28
·
answer #3
·
answered by Northstar 7
·
0⤊
0⤋
use parts, it will make your life easier.... equation is vu-Svdu
let u = (2x-3), du = 2, dv = (x-2)^(1/2), v = (2/3)(x-2)^(3/2),
ie, (2x-3)(2/3)(x-2)^(3/2) - S 2(2/3)(x-2)^(3/2)dx
(2x-3)(2/3)(x-2)^(3/2) - (4/15)(x-2)^(5/2)
2006-12-20 20:57:23
·
answer #4
·
answered by Mr.Math 1
·
0⤊
0⤋
[2xsqrt(-2x)(2x-5)]/5
2006-12-20 20:21:44
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋